Karakterisasi Î±-Amilase Bacillus firmus KH.9.4 Alkalotoleran dari Limbah Cair Tapioka - Rachmania, Nisa; Iswati, Ruma; Imas, Tedja (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2004)
Alkalotolerant bacteria identified as Bacillus firmus KH.9.4 was isolated from tapioca liquid waste from Kedung Halang, Bogor. The isolate showed optimum a-amylase activity after 15 hours of cultivation on liquid media. Optimum enzyme activity occurred at pH 6.0 and temperature 800C. Upon heat treatment at pH 6.0 and 800C the enzyme was still 100% active after 6 hours incubation without substrate. The enzyme activity was enhanced by supplement 10 mM MgSO4.7H2O. The presence of 1, 5, and 10 mM ethylenediaminetetraacetic acid demonstrated the inhibitory effect to this enzyme. Zymogram analysis revealed one translucent zone corresponding to soluble starch activities after 60 minutes of incubation at 400C in the 0.05 M phoshate buffer pH 7.0. Whereas SDS-PAGE analysis showed that there are 5 bands of proteins.